EDUCATION SIX STEPS OF HAND WASHING FOR ELEMENTARY SCHOOL STUDENTS - nisa dewanti; Kiki Widyasari (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
The six steps hand washing counseling activity given to grade five students at Rangkah Kidul Sidoarjo Elementary School is a form of community service in the form of presenting material and simulations which are expected to prevent disease in children. Implementation of counseling activities on January 26, 2023 at Rangkah Kidul Sidoarjo Elementary School. Target of this counseling activity is students of class 5A and 5B at Rangkah Kidul Sidoarjo Elementary School. Prior to carrying out extension activities, there is a process of preparing activities for approximately four weeks prior to implementation activities, starting from determining the type of extension to applying for permits to related parties. As a form of evaluation, the activity was attended by 47 grade five students, the participants took part in the activity with great enthusiasm, and the counseling activities ran smoothly.